Uterine dynamics, blood profiles, and electronic fetal monitoring of primiparous and multiparous bitches classified according to their weight - Lezama-García, Karina; Martínez-Burnes, Julio; Baqueiro-Espinosa, Uri; Villanueva-García, Dina; Olmos-Hernández, Adriana; Hernández-Ávalos, Ismael; Mora-Medina, Patricia; Domínguez-Oliva, Adriana; Mota-Rojas, Daniel (Frontiers in Veterinary Science, 2023)
Perinatal mortality occurs in all species. In dogs, mortality rates have been reported to range from 5 to 35%. Electronic fetal and uterine monitoring has recently been used in domestic animals to monitor the mother and newborn before and during parturition. In this way, the fetal heart rate and uterine dynamics can be monitored. This study evaluated the uterine dynamics of bitches with different weights and parity. Ninety-six bitches and their 476 puppies were divided into four experimental groups containing 24 individuals each (12 primiparous bitches and 12 multiparous bitches), according to body weight: G1 (4–8 kg), G2 (8.1–16 kg), G3 (16.1 to 32 kg), and G4 (32.1 to 39.6 kg). The fetal heart rate decelerations (dip 2 patterns), uterine dynamics, and bitches’ blood profiles were evaluated, including levels of glucose, lactate, pCO2, pO2, pH, HCO3−, and Ca++. The dam weight can affect the vitality of newborns and the uterine dynamics, with differences in the frequency, intensity, and duration of myometrial contractions. The expulsion interval between puppies was longest in primiparous bitches with low weight and shortest in multiparous bitches with high weight. The expulsion interval and the number of stillborn females were higher in primiparous bitches with high weight. Newborn male puppies were significantly heavier than newborn females.